A linguistics landscape of an Indonesian metropolitan spot: A glimpse over Braga - Inayah Wulandari; Khristianto Khristianto; Arbain Arbain (Faculty of Social and Political Sciences University of Bangka Belitung, 2022)
This paper analyzes and explores the use of language in public spaces using the field of linguistics landscape. The purpose is to indicate and analyze the linguistic landscape features of billboards, road signs, commercial shop signs, campaign posters, etc that found in Braga Street, Bandung City. Braga Street is one of the famous areas in Bandung because Braga has many unique buildings so that people, especially youngsters come to Braga even just to hang out. The data collected by the writer are virtual spaces using the Google Street View application. The writer explores the Braga Street area with that application and then takes screenshots of those signs. Qualitative descriptive conducted in this paper by applying Shohamy and Gorter’s theory which refers to the analysis of the characteristics of bilingual and multilingual signs to better understand the multi-ethnic and multi-cultural city. The result is the use of monolingual and bilingual signs dominates especially in the private sector. Sundanese is still maintained by the people as evidenced by the existence of signs that use the local language. English is a foreign language that is quite often used by sign makers in this Braga Street area. This is because English can attract visitors by giving an impression, especially in the economic sector as their marketing strategy. Although the multilingual aspect in the Braga area is still very minimal, it can still show that the use of language in public spaces (Braga Street) areas is already varied.